In search of moral politics: Kant cosmopolitan right in state’s sovereignty crises - Martin, Claudiu (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Regarding the relationship between right and morality, especially regarding cosmopolitan right, there is a tension. On the one hand, a number of commentators argue that there is a sharp distinction whereby morality should be subordinated to jurisdiction because the latter belongs to the public sphere, while the first one to the private sphere, and thus hospitality is linked to right; and, on the other hand, some argue that morality takes precedence by understanding hospitality as an ethos that is essential to achieving political integration and that goes beyond the legal sphere. After seeing how Kant grounds duties, I will analyse both perspectives with respect to the right of hospitality. It will then be seen that for Kant right and morality are indistinguishable except for one exception, namely, when it is the legislator who does not comply with the right and does not guarantee the three basic principles that underpin a civil constitution: freedom, equality, independence. It will be argued that this is a situation that is currently taking place, the sovereignty of the State has gone into crisis as it produces legislation contrary to what Kant thought would be the legal foundations because the State is not subject to accountability. Three possible solutions to this problem will be proposed based on Kant's thought. The first is civil disobedience protected by the criterion of publicity. Secondly, the ecological issue as creating an epistemological status that obliges us to act in accordance with the general will of the contemporary situation. Finally, generosity is proposed as a form of political action and a moral duty that has an extensive character insofar as the subject transforms himself and overlaps interests, enabling him to create reciprocal networks and unanticipated communities that conform to the categorical imperative and institute a form of law based on co-obligations.